CHALLENGES FACED BY STUDENTS IN LEARNING LISTENING COMPREHENSION IN SMAN 2 JENEPONTO - Sri Ayu Handayani; Nurdin Noni; Amra Ariyani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This research is qualitative research that aim to find out the challenges faced by the students in learning listening comprehension. The population of this study was the second-grade students in the school of SMAN 2 Jeneponto. The sample collection technique from this study used cluster random sampling consisting of 15 students. This research instrument uses interviews. The results of data analysis showed that various factors that cause students to have challenges in listening include; quality of recorded materials, cultural differences, accent, unfamiliar vocabulary, length and speed of listening, and external factors as noise from outside the classroom, unclear teacher voices, and sitting position are the challenges faced by the students in listening comprehension.Keywords— Challenges, Listening Comprehension, Learning English